Reactive oxygen species sources and biomolecular oxidative damage induced by aflatoxin B1 and fumonisin B1 in rat spleen mononuclear cells - Mary, Verónica Sofía (2012)
Aflatoxin B1 (AFB1) and fumonisin B1 (FB1) are mycotoxins widely found as cereal contaminants. Their immunotoxicities predispose to infectious diseases and may alter the tumor immune surveillance of human and animals, but the mechanisms underlying have not been fully elucidated, and the induction of oxidative stress has been proposed as a probable mechanism.This work was aimed at evaluating in spleen mononuclear cells (SMC) from Wistar rats the effects of the exposure, over cellular oxidative status, as well as at elucidating the contribution of different reactive oxygen species (ROS) to biomolecular oxidative damage, the biochemical pathways involved, and the probable interaction of both toxins to induce oxidative stress.All the treatments increased total ROS and oxidation of biomolecules, with MIX having the greatest effects. However, only MIX increased superoxide anion radical. The main ROS involved in oxidation of proteins, lipids and DNA appear to be hydrogen peroxide and hydroxyl radical. The mitochondrial complex I and CYP450 were involved in the ROS generation induced by all treatments. The NADPH oxidase system was induced by FB1 and MIX. The arachidonic acid metabolism contributed to the ROS formation induced by AFB1 and MIX. These results demonstrate that an interaction between AFB1 and FB1 occur in the oxidative stress induction, and show the biochemical pathways involved in ROS generation in SMC. The oxidative stress could mediate the AFB1 and FB1 individual and combined immunotoxicities.